The impact of chronic kidney disease on health-related quality of life (HRQoL): key insights from a hospital-based cross-sectional study - Gautam Sahu; Pooja Arora; Pramil Tiwari; Sanjay D’Cruz; Anita Tahlan (Brazilian Journal of Nephrology)
Abstract Introduction: This study explores the health-related quality of life (HRQoL) in chronic kidney disease (CKD) patients, analyzing the impact of socio-demographic factors (such as age, education, and income) and clinical factors (including disease stage, comorbidities, and treatment type). The study aims to assess factors for improving patient outcomes and enhancing the overall well-being of CKD patients. Methods: This cross-sectional study, conducted at the nephrology clinic of a public teaching hospital, involved 560 randomly selected participants. The Kidney-Disease Quality of Life-Short Form (KDQOL-SFTM) questionnaire was used to collect data, analyzed via SPSS (version 20.0). Descriptive statistics were used to summarize baseline characteristics. Cronbach’s α was used to assess the reliability of questionnaire items. Differences in HRQoL scores between groups were examined using independent t-tests and ANOVA, while regression analysis was used to explore associations between variables. Results: The study analyzed the HRQoL in 560 CKD patients, who had a mean age of 53.32 years and a response rate of 81.27%. The mean HRQoL score was 32.03 ± 6.55. Males predominated in early CKD stages (72.5% in stages 1 and 2), while females were more prevalent in stage 4. Unemployment was high (73.6%). Patients > 50 years scored higher on the Burden of Kidney Disease (BKD) scores (26.73 ± 19.36), while younger patients showed better mental health outcomes. Freshly diagnosed patients had better scores across HRQoL domains than known cases. Education significantly predicted higher HRQoL (p < 0.001), but occupation and income did not. Hypertension (75.71%) and diabetes (39.64%) were common comorbidities, underscoring socio-economic influences on HRQoL in CKD. Conclusion: This study highlights the strong impact of socio-demographic and clinical factors, particularly education, employment, and disease stage, on CKD patients’ HRQoL. Early interventions and holistic CKD management, addressing clinical and socio-economic issues, are crucial for enhancing patient well-being.